2004
DOI: 10.1111/j.1365-3040.2003.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Does turgor limit growth in tall trees?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
213
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(234 citation statements)
references
References 40 publications
18
213
2
1
Order By: Relevance
“…It is well known that low xylem water potentials cause detrimental effects on plant function by inducing xylem conduit embolism and turgor reduction in living cells (e.g. Tyree, 2003;Woodruff et al, 2004). This study suggested that decreasing xylem water potentials also limits sugar transport for a given phloem structure as water is held more tightly in the xylem (see Eq.…”
Section: Accepted Manuscript 26mentioning
confidence: 84%
“…It is well known that low xylem water potentials cause detrimental effects on plant function by inducing xylem conduit embolism and turgor reduction in living cells (e.g. Tyree, 2003;Woodruff et al, 2004). This study suggested that decreasing xylem water potentials also limits sugar transport for a given phloem structure as water is held more tightly in the xylem (see Eq.…”
Section: Accepted Manuscript 26mentioning
confidence: 84%
“…Todas estas respuestas tienen como consecuencia la disminución del crecimiento global de la planta y, por ende, una disminución en la acumulación de biomasa. El transporte de agua en la planta es una parte integral del proceso de crecimiento, ya que una variedad de procesos relacionados con el crecimiento, incluyendo la formación y expansión de células vegetales, son dependientes de la presión de turgencia y el volumen celular (Woodruff et al 2004). Por tanto, las relaciones existentes entre las variables hídricas, fotosíntesis y conductancia estomática son aspectos clave en la comprensión del proceso de tolerancia al estrés (Dickson y Tomlinson 1996), lo cual determina a su vez el crecimiento, reproducción, distribución y composición de especies vegetales.…”
Section: Introductionunclassified
“…Lower A at the same g s for tall versus short trees could also result from reduced g i . Thus, while hydraulics per se appear to play a direct role in driving diel gas exchange patterns, longer term impacts of hydraulics on g i or leaf [N] appear to also be critical (see also Le Roux et al 2001;Woodruff et al 2004;Lloyd et al 2009). Foliar D and p a − p c results for all seven Nothofagus sites showed evidence of lower p c as h increased (Table 10.1, Fig.…”
Section: The Response Of Leaf-level Gas Exchange and D To H In Nothofmentioning
confidence: 99%
“…This relationship sets boundaries on physiological properties that impact D. First, it sets an upper limit on foliar water potential during expansion, causing increasing leaf mass per unit area with increasing h (Marshall and Monserud 2003;Woodruff et al 2004;Koch et al 2004;Cavaleri et al 2010), which may subsequently influence g i and p c via shifts in mesophyll surface area (Terashima et al 2005;Oldham 2008). Second, as maximum xylem water potential declines with increasing h, the potential range of xylem water potential must also decline (unless the trees are anisohydric with h, which is rarely observed, allows only a few tenths MPa shift, and has consequences for xylem conductance and leaf area, Yoder et al 1994;McDowell et al 2002a).…”
Section: Why Does D Decline Linearly With Increasing H?mentioning
confidence: 99%
See 1 more Smart Citation